SKINCARE CREAM PREPARATION AND EVALUATION OF PARE (MOMORDICA CHARANTIA) LEAVES USING THREE DIFFERENCE BASE - INDRAWATI, TETI; HAJARD, ISMAYANTI; PRATAMI, DIAH KARTIKA (International Journal of Applied Pharmaceutics, 2020)
Objective: The purpose of this research is to make a skincare cream that contains bioactive from Momordica charantia leaves (MCL) using three kinds of base cream. Methods: The dried MCL made into powder shape and then extracted using 96% ethanol solvent. The liquid extract was evaporated using a vacuum evaporator until obtained by the viscous extract. The Momordica charantia leaves ethanol extract (MEE) with a concentration of 4.00% made into a cosmetic product used vanishing, cold, and hand and body cream as a base. Creams made by mixing the oil phase and water phase at 70 °C until cream mass formed, then added MEE at 40 °C. All the product creams were evaluated their physical and chemical characteristics and stability tested. Results: Cream of Momordica charantia leaf ethanol extract had semisolid form, yellowish color, the peculiar smell of Momordica charantia ethanol extract, homogeneous, pH 6.37-6.67, easily spread with spreading ability 2,081.21-2,835.43 mm2, has viscosity 125,000-18,0000 cps and stable 3 mo in a room and 60 °C temperature storage. Conclusion: Momordica charantia leaves can be made become a good cream for skincare cosmetics that more beneficial and profitable than as waste. This skincare creams using vanishing base cream, cold cream, and hand and body cream as base creams.